To assess the effective and safety of compound glutamine entersoluble capsules in irritable bowel syndrome: A protocol for systematic review and meta-analysis. Issue 10 (12th March 2021) - Zhang, Yong; Liu, Ru; Wang, Jin; Yan, Shuguang; Guo, Zhiqing
Abstract: Background: Irritable bowel syndrome (IBS) is one the common medical condition of functional GI disorder (FGD) characterized by bowel-related symptoms without other organic gastrointestinal (GI) disease. Compound Glutamine Entersoluble Capsules(CGEC), a compound preparation in which each capsule contains 120 mg L-glutamine, 50 mg ginseng, 50 mg licorice, 50 mg Atractylodes macrocephala and 50 mg Poria cocos, have been reported the efficacy of CGEC for patients with IBS in improving the clinical symptoms and quality of patients' life. However, there is no a systematic review related to CGEC for IBS to this day. In this study, we will systematically evaluate the effectiveness and safety of CGEC in the treatment of IBS-D with a meta-analysis method, so as to provide a solid evidence for clinical practice. Methods: In this study, a literature search was performed by using the Chinese and English databases, which include PubMed, Embase, MEDLINE, Cochrane Library Central Register of Controlled Trials, China National Knowledge Infrastructure (CNKI) database, Wanfang Data Knowledge Service Platform, the VIP information resource integration service platform (cqvip), China Biology Medicine Disc (Sino Med), and the Chinese Clinical Trial Registry (ChiCTR), to find the related literature of CGEC in the treatment of IBS published from the inception date of each predefined database upto January 2021. The evaluation of the risk of bias for eligible studies will be performed by two investigators. Data synthesis will be performed by RevMan 5.4 software. Heterogeneity between studies can be assessed by a heterogeneity X2 test. The degree of heterogeneity among multiple included studies can be measured by I 2 . The stability of systematic review or meta-analysis outcomes will be evaluated by Sensitivity analysis. Reporting bias will be evaluated by funnel plot. Finally, The Grading of Recommendations Assessment, Development and Evaluation (GRADE) will be used to assess the quality of evidence obtained. Results: The results of this study will be published in a peer-reviewed journal. Conclusion: Whether it is the effectiveness and safety of CGEC in the treatment of IBS will be judged in the result of this systematic review.